COVID-19 in Ghana: challenges and countermeasures for maternal health service delivery in public health facilities - Agbozo, Faith; Jahn, Albrecht (Reproductive health, 2021)
We provide a situational update on COVID-19 in Ghana, the seventh African country reporting the most cases. Some modifications occurring within the health system to curtail the outbreak and its potential impact on the delivery of antenatal care services are also highlighted. With the discovery of the Delta variant in Ghana, the current attention is to prevent a third wave of infection, and also control and manage existing cases. Efforts to procure vaccines, vaccinate special populations and sensitize the public on the implications of vaccine hesitancy are ongoing. Amidst these activities, we suggest some innovations and countermeasures to safeguard primary healthcare services and potentially reinvest efforts towards achieving the sustainable development goal three within the context of maternal healthcare, citing examples specific to developing countries.